2011
DOI: 10.1073/pnas.1016060108
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial complex II has a key role in mitochondrial-derived reactive oxygen species influence on plant stress gene regulation and defense

Abstract: Mitochondria are both a source of ATP and a site of reactive oxygen species (ROS) production. However, there is little information on the sites of mitochondrial ROS (mROS) production or the biological role of such mROS in plants. We provide genetic proof that mitochondrial complex II (Complex II) of the electron transport chain contributes to localized mROS that regulates plant stress and defense responses. We identify an Arabidopsis mutant in the Complex II subunit, SDH1-1, through a screen for mutants lackin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
191
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(200 citation statements)
references
References 45 publications
6
191
1
2
Order By: Relevance
“…This limitation changed when a point mutation of SDH1-1 (dsr1) was identified that did not knockout SDH, but instead lowered SDH activity and decreased mitochondrial ROS production. It was first identified as a mutant that had lost salicylic acid (SA)-but not H 2 O 2 -dependent stress response using a GST GSTF8 promoter stress response assay (Gleason et al, 2011). The dsr1 mutant showed steadystate decrease expression of peroxidases, glutaredoxins, and trypsin and protease inhibitor family genes and reduced expression on SA induction of a set of SA-responsive genes normally induced in response to exposure of Arabidopsis to bacterial, fungal, or viral pathogens (Gleason et al, 2011).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This limitation changed when a point mutation of SDH1-1 (dsr1) was identified that did not knockout SDH, but instead lowered SDH activity and decreased mitochondrial ROS production. It was first identified as a mutant that had lost salicylic acid (SA)-but not H 2 O 2 -dependent stress response using a GST GSTF8 promoter stress response assay (Gleason et al, 2011). The dsr1 mutant showed steadystate decrease expression of peroxidases, glutaredoxins, and trypsin and protease inhibitor family genes and reduced expression on SA induction of a set of SA-responsive genes normally induced in response to exposure of Arabidopsis to bacterial, fungal, or viral pathogens (Gleason et al, 2011).…”
mentioning
confidence: 99%
“…It was first identified as a mutant that had lost salicylic acid (SA)-but not H 2 O 2 -dependent stress response using a GST GSTF8 promoter stress response assay (Gleason et al, 2011). The dsr1 mutant showed steadystate decrease expression of peroxidases, glutaredoxins, and trypsin and protease inhibitor family genes and reduced expression on SA induction of a set of SA-responsive genes normally induced in response to exposure of Arabidopsis to bacterial, fungal, or viral pathogens (Gleason et al, 2011). The dsr1 mutant also had higher susceptibility to fungal and bacterial pathogens, indicating that mitochondrial SDH is involved in response to biotic stress in vivo in plants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These studies demonstrate the importance of the complex modulation of plant metabolism and defense responses during pathogen infection. These changes activate a series of biological signaling mechanisms such as Ca 2ϩ influx (8,9), kinase cascades (10,11), reactive oxygen species (12,13), and phytohormone signaling pathways (14). However, so far none of these studies has addressed quantitative changes of grapevine protein post-translational modifications (PTMs) 1 upon pathogen infection, which we believe would provide novel insights into the underlying molecular processes that may eventually yield novel strategies for pathogen control in the field.…”
mentioning
confidence: 99%
“…Mitochondria are among the multiple organelles that contribute to ROS production. Mutants defective in mitochondrial ROS (mROS) generation exhibit enhanced disease susceptibility to specific fungal and bacterial pathogens 34 . All these studies point to a positive regulatory role of mitochondria during immune responses through ROS generation.…”
Section: Nature Communications | Doi: 101038/ncomms3558mentioning
confidence: 99%